The influence of climate change knowledge on consumer valuation of sustainably produced rice in Vietnam - Connor, Melanie; Demont, Matty; Sander, Björn Ole; Nelson, Katherine; Ong Quoc Cuong (Elsevier, 2022)
Rice production in Vietnam is characterized by environmental degradation, high greenhouse gas emissions, and low wage rates. The Sustainable Rice Platform (SRP) standard is the first globally recognized certified sustainable production standard for rice. There are efforts to increase sustainability in rice production, but little is known about consumer perception of sustainability labels. This study investigates the relationship between climate change knowledge and consumer willingness to pay for SRP-certified rice in Vietnamese supermarkets. The results show that consumers are willing to pay on average a 29% price premium for SRP-labelled rice. Increased knowledge about climate change and higher income positively influence the amount consumers are willing to pay. The results have policy and market implications for scaling production and consumption of rice complying with certified sustainable production standards in Vietnam.